Migration and urbanization in Brazil from the 1950s: a brief history and reflection in the light of migration theories (Revista Espinhaço, 2019)
The understanding of the spatial (re)distribution mechanisms of the Brazilian population is a great challenge for geographers, economists, demographers and scholars from several other areas of knowledge today, given its magnitude and complexity. This paper aims to provide a brief history of migrations and urbanization in Brazil from the 1950s onwards, based on a bibliographical review. The processes of redistribution of the population in the territory and the reconfiguration of the national urban system were evaluated in the light of the main migration theories, used as a tool for interpretation and analysis. The basic foundations of these theories, their convergences, divergences and applicability to the Brazilian case are discussed throughout the text. The debate on the relationship between migrations and development and the effects of the demographic transition on internal migrations were discussed, among other issues.
Keywords: Internal migration; urbanization; migration theories